Fundamentals of Esthetic Facial Plastic Surgery - Viterbo, Fausto [UNESP]; Neto, Balduíno [UNESP]; Magnani, Lucas [UNESP] (Springer Nature, 2024)
Surgical procedures for aesthetic purposes of the face have evolved along with a better understanding of the anatomy and physiology of tissue aging. The face and neck lift are now no longer just aimed at the resection and tightening of skin and fat, but a remodeling and repositioning of the tissues to achieve a more youthful and pleasant contour. Based on the following fundamentals, the surgeon will have in his hands knowledge that will give him more confidence and ability to perform the different techniques described in the literature today, achieving predictable and lasting results.